PEMANFAATAN EKSTRAK TERSTANDARDISASI DAUN SOM JAWA (Talinum paniculatum (Jacq.) Gaertn) DALAM SEDIAAN KRIM ANTIBAKTERI Staphylococcus aureus - Wahyuning Setyani; Hanny Setyowati; Dewi Ayuningtyas (Sanata Dharma University, 2016)
Infectious diseases have been the leading cause of morbidity and mortality because of the widespread antibacterial resistance due to existing drugs. Thus, the discovery and development of new antimicrobial agents, especially from natural resources is important to promote the human health.This research aimed to examine the antibacterial activity of som jawa (Talinum paniculatum (Jacq.) Gaertn.) standardized extract thus their application into cream. Extraction was done by remaceration method, then followed by phytochemical investigation to obtain the active ingredients inside extract. The result of this research showed that both som jawa standardized extract and their formula cream had antibacterial activity towards Staphylococcus aureus. This formula cream was potential as alternative herbal medicine for skin infection caused by Staphylococcus aureus.